The cnidome and internal morphology of Lophelia pertusa (Linnaeus, 1758) (Cnidaria, Anthozoa). (21st June 2016) - Strömberg, Susanna M.; Östman, Carina
Abstract: The cnidome of the scleractinian cold‐water coral Lophelia pertusa (Linnaeus, 1758, syn. Lophohelia prolifera ) was described by Carlgren in 1940. Due to a renewed interest in the cnidae of L. pertusa, specifically comparisons of adult and larval cnidae and their functions, we now redescribe the cnidome from material collected at the Tisler reef in Norway, close to Carlgren's collection site at Saekken (Sweden). Cnidae from column, tentacles, actinopharynx, mesenterial filaments and acontia were investigated. Fresh tissue preparations were compared to histological preparations of decalcified polyps to verify the presence of cnidocysts and secretory cells, and their composition and organization within tissues. The cnidome included microbasic b‐mastigophores, microbasic and mesobasic p‐mastigophores, holotrichous isorhizas and spirocysts. The nematocyst type cnidae (b‐, p‐mastigophores, isorhizas) appeared in different size classes with different distributions within the tissue. Spirocysts were highly variable in shape and size, without distinct size classes. In addition, developing stages of cnidae were documented, with new observations on the succession of p‐mastigophore shaft development. The present observations were in general congruent with the cnidocyst descriptions from L. prolifera made by Carlgren; however, a tiny cnida, possibly of isorhiza type, has been added. Finally, the use of the term acontia is discussed.